Fructanolytic and saccharolytic enzymes of the rumen bacterium Pseudobutyrivibrio ruminis strain 3--preliminary study - Kasperowicz, A; Stan-Glasek, K; Guczynska, W; Piknová, M; Pristas, P; Nigutová, K; Javorský, P; Michałowski, T (Folia microbiologica, 2010)
P. ruminis strain 3 was isolated from the ovine rumen and identified on the basis of comparison of its 16S rRNA gene with GenBank. The bacterium was able to grow on Timothy grass fructan, inulin, sucrose, fructose and glucose as a sole carbon source, reaching absorbance of population in a range of 0.4-1.2. During 1 d the bacteria exhausted 92-97% of initial dose of saccharides except for inulin (its utilization did not exceed 33%). The bacterial cell extract catalyzed the degradation of Timothy grass fructan, inulin and sucrose in relation to carbon source present in growth medium. Molecular filtration on Sephadex G-150, polyacrylamide gel electrophoresis combined with zymography technique and TLC was used to identify enzymes responsible for the digestion of sucrose and both polymers of fructose. Two specific endolevanases (EC 3.2.1.65), nonspecific beta-fructofuranosidase (EC 3.2.1.80 and/or EC 3.2.1.26) and sucrose phosphorylase (EC 2.4.1.7) were detected in cell-free extract from bacteria grown on Timothy grass fructan.
Keywords: Enzymes; bachor; DNA bakterií; DNA, Ribosomal; Phylogeny; fruktany; Sequence Analysis, DNA; Fructans; Molecular Sequence Data; molekulární sekvence - údaje; RNA ribozomální 16S; Cluster Analysis; Rumen; sacharosa; zvířata; enzymy; bakteriální proteiny; RNA, Ribosomal, 16S; inulin; Phleum; sekvenční analýza DNA; Inulin; DNA, Bacterial; Cattle; fylogeneze; Chromatography; skot; shluková analýza; Bacterial Proteins; chromatografie; Sucrose; ribozomální DNA; grampozitivní bakterie; Animals; Gram-Positive Bacteria